Statistical Approach for Production and Price Analysis for Varieties of Mango of South Gujarat - Shah, Neepa; Naik, Shefali (Vidyapith (વિદ્યાપીઠ), 2024)
Mango is the main fruit crop having a major share in socio-economic development of South Gujarat. Price of the crop varies every year so to find the parameters that affect the production and price, we have conducted a study. We have collected the data for the year 2013-14 to 2021-22 of the production of mango for the study where we found sudden increase and decrease in the price of this crop. During the investigation, we found that there are other affecting factors for varieties of mango. Hence, the study is based on the factors that are affecting mango price and production such as production area, temperature and humidity during the flowers setting season to fruit generation. Besides these, we also determined the huge gap between two consecutive years’ mango production and during the pandemic COVID-19 there are changes in the production and price. While analyzing data of the mango production on the basis of collected data shows that the production is not consistent over the years in the same areas and is affected by the weather conditions like very heavy rainfall or low rainfall including other external parameters. The result of the investigation is prepared using regression analysis. Line chart analysis is also done for various types of mangoes to understand increase or decrease of the price during relevant year. The study was carried out from the data of selling price of the mango at cooperative society of the South Gujarat where farmers have large orchards of mango.